2020
DOI: 10.1021/acs.joc.0c01124
|View full text |Cite
|
Sign up to set email alerts
|

Triggering the Antitumor Activity of Acyclic Enediyne through Maleimide-Assisted Rearrangement and Cycloaromatization

Abstract: Acyclic enediynes are generally inactive under physiological conditions to be used as antitumor agents like their natural enediyne counterparts. A new mechanism named as maleimide-assisted rearrangement and cycloaromatization (MARACA) is uncovered to trigger the reactivity of acyclic enediynes. Through this mechanism, cascade 1,3-proton transfer processes are accelerated with the maleimide moiety at the ene position to enable the acyclic enediynes to undergo cycloaromatization and generate reactive radicals un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 74 publications
2
40
0
Order By: Relevance
“…[12] Recently, we uncovered a new mechanism named as maleimide-assisted rearrangement and cycloaromatization (MARACA) to trigger the antitumor activity of acyclic enediynes through the facilitated tautomerization of enediyne to enyne-allene and the generation of radical species under physiological conditions. [13] We also found that the phenyl radical formed from MSC could underwent 5-endo ring closure to form a stable product, suggesting the presence of different pathways of the diradical intermediates beside hydrogen-abstracting reactions. Along the same line, we designed enediyne 1 with acid-labile protecting groups which could be converted to enyne-allene 2 and 3 in the present of trifluoroacetic acid (TFA) at 0°C (Scheme 1).…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…[12] Recently, we uncovered a new mechanism named as maleimide-assisted rearrangement and cycloaromatization (MARACA) to trigger the antitumor activity of acyclic enediynes through the facilitated tautomerization of enediyne to enyne-allene and the generation of radical species under physiological conditions. [13] We also found that the phenyl radical formed from MSC could underwent 5-endo ring closure to form a stable product, suggesting the presence of different pathways of the diradical intermediates beside hydrogen-abstracting reactions. Along the same line, we designed enediyne 1 with acid-labile protecting groups which could be converted to enyne-allene 2 and 3 in the present of trifluoroacetic acid (TFA) at 0°C (Scheme 1).…”
Section: Introductionmentioning
confidence: 69%
“…The reactants were chosen to be AI and BI in Figure 2 (similar to compound 2 and 3 albeit with the benzyl group at the maleimide moiety being replaced with methyl group to reduce calculation burden). The previous reports from our group and other groups had demonstrated that such a computational setup was suitable for enediyne systems [8f,13–14,20] . Unrestricted DFT method together with broken symmetry ansatz was employed in the structure optimizations of transition states in MSC and the resulted diradical products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 3 has two phenylethynyl groups at the ortho positions of benzene. It is known that an enediyne moiety is capable of inducing Bergman‐type cyclization, 21,22 causing irreversible double‐stranded DNA scission, when the distance between two triple bonds is smaller than 3.4 Å. However, compound 3 , with a diyne structure, did not significantly inhibit E. coli growth; neither did compound 4 , with two phenylethynyl groups at the para positions, nor compound 5 , with no central benzene ring, significantly inhibited E. coli growth at all.…”
Section: Figurementioning
confidence: 98%
“…[27] Following this line, a new mechanism named as maleimide-assisted rearrangement and cycloaromatization (MARACA) to trigger the antitumor potency of enediynes was proposed recently. [28] Moreover, the interception pathways by intramolecular hydrogen atom transfer (HAT) with regard to highly reactive diradicals generated through MARACA have been uncovered, [29] which clearly indicated that the intramolecular HAT pathways to consume the diradical species have posed a challenge to further boost their biological activity unless the enediyne molecules are elaborately designed. On the other hand, because of the involvement of the essential MSC step in the MARACA mechanism, the dual reactivity of the intermediates from cycloaromatization is expected to show up.…”
Section: Introductionmentioning
confidence: 99%